Food Safety: Technologies and Governance - Terziev, Dimitar; Zhou, Pei; Terziyska, Ralitsa; Zhang, Dan (UNWE Yearbook, 2018)
This study is a result of collaboration between Chinese and Bulgarian researchers during the last few years in the field of environmental economics and food safety. Suitable technologies in the area are developed. Yet proper economic models for their practical applications are still missing. The so called ecological agriculture is a tale of frauds and wasted public funds. Most of the studies and research in field are also not good enough.In our analysis we apply the methodology of the New Institutional Economics School in order to interpret and outline the economic logic of the manner in which real ecological farmers manage their business relations. We describe the economic sense lying behind their activities that could be improve their understanding of their essence and guide them how to carry out the much needed institutional modernization. This would will be useful every individual and for the society at large. This paper, as well a few others published over the last two years, is an early attempt for modern, economic examination of environment-friendly agriculture (with a special focus on food safety) and its sustainability.
Keywords: China; Bulgaria; Food safety; Transaction costs; Governance modes